Personal factors, discord with mother-in-law, spousal support and marital satisfaction amongst Chinese women in Selangor - Juhari, Rumaya; Chew, Wei Ye (2012)
Marital satisfaction has been acknowledged as a strong determinant of quality of life and highly related with mental and physical health status of individuals. Hence, understanding factors that influence marital satisfaction is crucial in order to ensure a well-balance human being. Using data on 400 married Chinese women in Selangor, this study aims to examine the relationships between personal background factors, discord with mother in-law, and spousal support with marital satisfaction. Established and pilot tested instruments were used to measure the key variables in this study. Bivariate analyses revealed that level of education (r= 0.15), individual income (r=0.16), family income (r=0.22), extraversion (r=0.26), agreeableness (r=0.36), conscientiousness (r=0.24), neuroticism (r= -0.24), openness to experience (r=0.43), spousal support (r=0.48) and conflict with mother-in-law (r=-0.56) were significantly related to marital satisfaction. Furthermore, family income (β= 0.134), extraversion (β=-0.135), agreeableness (β=0.176), openness to experience (β= 0.289), spousal support (β=0.367) and conflict with mother-in-law (β=-0.407) were significant predictors of marital satisfaction. Findings from this study emphasized the importance of positive personality traits, spousal support and the negative influence of conflict with the mothers-in-law on marital satisfaction of the respondents.